2015
DOI: 10.1017/jfm.2015.643
|View full text |Cite
|
Sign up to set email alerts
|

Probing the nanoscale: the first contact of an impacting drop

Abstract: When a drop impacts a solid surface, the lubrication pressure in the air deforms its bottom into a dimple. This makes the initial contact with the substrate occur not at a point but along a ring, thereby entrapping a central disc of air. We use ultra-highspeed imaging, with 200 ns time resolution, to observe the structure of this first contact between the liquid and a smooth solid surface. For a water drop impacting onto regular glass we observe a ring of micro-bubbles, owing to multiple initial contacts just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 31 publications
5
36
0
1
Order By: Relevance
“…These bubbles are formed by an instability of the moving contact line but note that due to the cylindrical symmetry of our calculations these bubbles are in fact tori that would be unstable in 3D. These bubbles are similar to those observed in numerical simulations of drop impacts on a thin liquid film ) and reminiscent of experimental observations by Li et al (2015b). How these bubbles would fare under refinement of the grid has not been investigated but their size would likely vary.…”
Section: Scaling Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…These bubbles are formed by an instability of the moving contact line but note that due to the cylindrical symmetry of our calculations these bubbles are in fact tori that would be unstable in 3D. These bubbles are similar to those observed in numerical simulations of drop impacts on a thin liquid film ) and reminiscent of experimental observations by Li et al (2015b). How these bubbles would fare under refinement of the grid has not been investigated but their size would likely vary.…”
Section: Scaling Analysissupporting
confidence: 68%
“…Measuring these quantities experimentally remains a difficult challenge because of the small values of the Stokes numbers but this has been done eventually using complex optical techniques (Driscoll & Nagel 2011;Kolinski et al 2012;Bouwhuis et al 2012;Klaseboer et al 2014;Li et al 2015a). The results are somehow puzzling since the theoretical predictions have not always been observed or only in a narrow range of Stokes numbers.…”
Section: /3mentioning
confidence: 99%
“…This was observed in early imaging (24) and speculated to be due to micro-bubbles. With the high-speed interferometry we have indeed verified this hypothesis and shown that the roughness of the solid plays a key role in this entrapment of the ring of micro-bubbles (26) . Figure 3 (26) .…”
Section: First Contact Of a Drop Impacting On A Surface With Nano-metsupporting
confidence: 56%
“…Finally, in this experiment we showed that for very low impact velocity the water drop can glide on the air-layer without initial contact between the two liquids. The breakup of this thin air-layer was observed with a spatial resolution of 0.6 µm/px and a time resolution of 200 ns, showing the details of this breakup process in unprecedented detail (26) . This breakup leaves behind a wide axisymmetric band of micro-bubbles (see their figure 5).…”
Section: First Contact Of a Drop Impacting On A Surface With Nano-metmentioning
confidence: 97%
See 1 more Smart Citation